Representation of Insult in Instagram Comment Column @gibran_rakabuming Post-Nomination as Vice Presidential Candidate: A Forensic Linguistic Study - Mukhibun, Akhmad; Saputri, Nanda Dewi; Sumarlam (Jurnal Sastra Indonesia, 2024)
Indonesia is holding the 2024 presidential and vice presidential elections, a 5-year agenda to elect the leaders of the Indonesian State. However, political events occur in the 2024 election series; one is the Constitutional Court's decision Number 90/PUU-XXI/2023, which allows presidential and vice presidential candidates to register before age 40 if they have served or are currently serving as regional heads. This study aims to describe hate speech as insults in the Instagram @gibran_rakabuming comment section after he is appointed a vice presidential candidate and its legal implications. This research is qualitative research with a forensic linguistic approach. The research data are lingual units in words, phrases, clauses, sentences, and texts. The data source was obtained through the Instagram @gibran_rakabuming comment column from November 13, 2023, to November 30, 2023, and ITE Law Number 19 of 2016. The data collection technique was carried out using listening and noting. The sampling technique was carried out by purposive sampling, namely by considering insult content, criminal elements, and relevance to the ITE Law regarding insulting hate speech. The data analysis technique uses the referential pairing method, which is an analysis technique that connects the form of insult with the criminal content in the ITE Law. The data validity technique uses data source triangulation. The results showed various insults in @gibran_rakabuming's comments section, namely in words, phrases, clauses, sentences, and texts. The insults are related to his status as a vice presidential candidate. The insults are in the form of curses, ridicule, disrespectful expressions, innuendo, and others. The legal implications of the ITE law were found in the form of mild, moderate, and severe insults. This research is expected to help identify legal cases related to language and can enrich the science of forensic linguistics.